2003
DOI: 10.1021/op0200625
|View full text |Cite
|
Sign up to set email alerts
|

A One-Pot Efficient Process for 16-Dehydropregnenolone Acetate

Abstract: A one-pot eco-friendly and efficient transformation of steroidal sapogenin diosgenin (1) and solasodine (2) to a commercially very important drug intermediate 16-dehydropregnenolone acetate (16-DPA, 9) was developed with an overall yield of 75%. This process can easily be exploited for industrial production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…IR spectrum exhibited a band at 1715 cm -1 for this newly generated carbonyl functionality. 13 C NMR & microanalyses were in conformity with its molecular structure and formula C 31 H 46 O 7. Although some literature reveal the application of other oxidant like hydrogen peroxide in presence of catalyst/phase transfer catalysts etc [14]. CrO 3 is still regarded as an oxidant of choice, because of its high efficacy and low cost.…”
Section: Step1mentioning
confidence: 99%
See 3 more Smart Citations
“…IR spectrum exhibited a band at 1715 cm -1 for this newly generated carbonyl functionality. 13 C NMR & microanalyses were in conformity with its molecular structure and formula C 31 H 46 O 7. Although some literature reveal the application of other oxidant like hydrogen peroxide in presence of catalyst/phase transfer catalysts etc [14]. CrO 3 is still regarded as an oxidant of choice, because of its high efficacy and low cost.…”
Section: Step1mentioning
confidence: 99%
“…are synthesized from 16-dehydropregnenolone acetate (16-DPA) 1, barring a few which are obtained by total synthesis. The plant origin compounds solasodine 2 and its oxygen analogue diosgenin 3 ( Figure 1) are the two main ingredients from which 16-DPA is generally synthesized [4][5][6][7][8][9][10][11][12][13][14][15]. Due to the favorable climatic condition of North East region of India, diosgenin yielding dioscorea species of plants, viz., D. compositae and D. floribunda grow abundantly in the region which led us to investigate commercial exploitation of these plants through large scale production of 16-DPA starting from diosgenin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can give origin to the compound 3-B-acetoxypregna-5-16-dienone, key starting source for progesterone production 1 and the compound 16-dehydroepiandrosterone, key starting source for androgen production 2 . Previous studies demonstrated that solasodine promotes antispermatogenic activity when administered to dogs (20 mg/kg for 30 days) 3 and to monkeys (150 mg/kg for 150 days) 4 .…”
Section: Introductionmentioning
confidence: 99%